Preparation and investigation of phosphate glass fibres and organic coupling agents for fully resorbable PGF/PCL composites - Tan, Chao (2018)
The work described in this thesis explored the manufacturing of fully resorbable high strength glass fibres as the reinforcement of poly-ε-caprolactone (PCL) composites and attempted chitosan and 3,4-Dihydroxy-L-phenylalanine (L-DOPA) as coupling agents to improve the interface of PGF/PCL composites. Phosphate based glasses (PBGs) in the system of P2O5-B2O3-Na2O-CaO-MgO-Fe2O3 were studied on their structural, thermal and degradation properties. The results of the experiments conducted revealed that the glass transition temperature, density and chemical durability were increased with increasing iron oxides in PBGs at the expense of CaO/MgO. The analysis of glass stability indicated that higher CaO/MgO ratios would have a positive effect on the fibre drawing from the glasses investigated. Fibres were produced from the glasses investigated using a melt drawn system and the effect of composition on the mechanical and degradation properties of the fibres were evaluated. Addition of Fe2O3 showed a significant improvement on the mechanical properties (tensile strength and modulus) and chemical durability of the fibres. Annealing treatment also enhanced the Young’s modulus and chemical durability of the fibres, while a reduction in tensile strength of the fibres was observed after annealing. Chitosan (CS) dissolved in dilute acetic acid solution was observed to significantly improve the interface of PGF/PCL composites. Coating of CS also showed a significant effect on glass surface protection, resulting in a maintaining of mechanical strength of the fibres in dilute acid solution. TG, SEM, FTIR, Raman and XPS were used to characterize the fibre surface. The results of XPS revealed a threshold value for CS concentration to improve the interface of the composites. L-DOPA dissolved in Tris buffer solution could also improve the interfacial properties of PGF/PCL composites. Meanwhile, a sufficiently high L-DOPA concentration within 0.02-0.04 g/mL could significantly enhance the tensile strength of the fibres. TG, SEM, FTIR and XPS were used to characterize the fibre surface. The results of these analyses suggested the zwitterionic form for L-DOPA powders and the melanin-like polymer layer on the fibres after coating.